Liberdade na lei ou na marra: as ações de liberdade dos escravos em Itambé-PE (1871-1888). - Silva, Rosildo Henrique da (2019)
This work analyzes freedom actions in the city of Itambé-PE between 1871 and 1888. The enslaved were in constant struggle to get their hands off, and one of the means were the actions in court in order to get the manumission after the promulgation. abolitionist laws that allowed the right of slaves to access justice. Two laws were very important for this process: the Free Belly of 1871, which freed children born from it, and the 1885 Sexagenarians, from which older people over 60 would be free. This paper aims to problematize the knowledge of the performance of the enslaved in the judicial sphere and to demonstrate that they were not passive people before their reality, but agents. The methodology used was the research and analysis of documents in the archives of the Justice Memorial in Pernambuco and the Itambé City Forum, where there are several freedom actions. Through qualitative and quantitative analysis, we highlight the struggle of slaves for their freedom, highlighting the case studies such as Camilo, João Francisco, Rita, etc. Most liberty actions refer to the Emancipation Fund, which managed to free some slaves, even if there were frauds; however, the enslaved continued to use it. The names and voices of the captives were present in this dissertation. Men and women united in the struggle to conquer the longed for manumission.